Gesture politics or real commitment? Gender inequality and the allocation of aid - Axel Dreher; Kai Gehring; Stephan Klasen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Donors of foreign aid increasingly claim to consider gender inequality in the recipient countries to be a serious concern. While aid specifically to promote gender equality receives only a tiny share of aid budgets, allocations to education, health, and civil society projects could be affected by gender inequality concerns. In this paper, we investigate whether donors indeed give more aid to countries with larger gender gaps ('need') in education, health, employment, or women's rights, or rather reward improvements in those indicators ('merit'). We find some evidence that gender gaps in education and health affect the allocation of aid in those sectors and overall, while greater female political representation appears to be 'rewarded' with higher aid flows; employment gaps do not seem to affect the allocation of aid. Taking account of substantive and statistical significance, overall, there is modest evidence that gender gaps affect the allocation of aid in total and for particular sectors. The quantitative effects are rather small in size and differ by donor country (group) and donor as well as recipient characteristics.
Keywords: F35; O11; O19; 330; aid allocation; gender inequality; sector-specific aid